Neuropsychiatric Symptoms in Posterior Cortical Atrophy and Alzheimer Disease - Suárez-González, Aida (J Geriatr Psychiatry Neurol, 2016)
BACKGROUND: Posterior cortical atrophy (PCA) is a rare neurodegenerative syndrome characterized by early progressive visual dysfunction in the context of relative preservation of memory and a pattern of atrophy mainly involving the posterior cortex. The aim of the present study is to characterize the neuropsychiatric profile of PCA. METHODS: The Neuropsychiatric Inventory was used to assess 12 neuropsychiatric symptoms (NPS) in 28 patients with PCA and 34 patients with typical Alzheimer disease (AD) matched by age, disease duration, and illness severity. RESULTS: The most commonly reported NPS in both groups were depression, anxiety, apathy, and irritability. However, aside from a trend toward lower rates of apathy in patients with PCA, there were no differences in the percentage of NPS presented in each group. All those patients presenting visual hallucinations in the PCA group also met diagnostic criteria for dementia with Lewy bodies (DLB). Auditory hallucinations were only present in patients meeting diagnosis criteria for DLB. CONCLUSION: Prevalence of the 12 NPS examined was similar between patients with PCA and AD. Hallucinations in PCA may be helpful in the differential diagnosis between PCA-AD and PCA-DLB.